A randomized study of cellphone technology to reinforce alcohol abstinence in the natural environment. (30th January 2013) - Alessi, Sheila M.; Petry, Nancy M.
Abstract Aims Contingency management (CM) uses tangible incentives to systematically reinforce abstinence and is among the most efficacious psychosocial substance abuse treatments. This study assessed the feasibility and initial efficacy of a portable CM procedure designed to address technical limitations for detecting drinking that have prevented using CM for alcohol problems. Design Participants received a cellphone, breathalyzer and training on video‐recording alcohol breath tests (BrACs) and texting results. For 4 weeks, staff texted participants one to three times daily indicating that a breath alcohol concentration test (BrAC) was due within the hour. Participants were randomized to (1) modest compensation for submitting dated time‐stamped BrAC videos regardless of results or (2) the same plus CM with escalating vouchers for on‐time alcohol‐negative tests (n‐BrAC; <02 g/dl). 'Thank‐you' texts were sent, with CM patients also informed of results‐based earnings. Setting Participants' natural environment. Participants Adults (n = 30; ≥ 21 years) who drank frequently but were not physiologically dependent. Measurements Drinking and related problems were assessed at intake and week 4. BrACs and self‐reports of drinking were collected throughout. The primary outcome was the percentage of n‐BrACs. Other outcomes were the longest duration of consecutive n‐BrACs (longest duration of abstinence) and self‐reports of drinking. Findings On average, 88.6% (10.4%) of BrACs were submitted on time, without group differences (P = 0.18). The percentage of n‐BrACs and LDA were greater with CM, and there was an interaction effect on drinking frequency and negative consequences, with decreases over time with CM (P = 0.00; effect sizes d = 0.52–0.62). Conclusion Cellphone technology may be useful for extending contingency management to treatment for alcohol problems.